Protecting the Village Credit Institution: Should Traditional Communities Adopt Modern Financial Management Practices? - Luh Putu Yeyen Karista Putri; Eric Gordon Withnall (Faculty of law Udayana University, 2018)
A Lembaga Perkreditan Desa (Village Credit Institution or LPD) is a type of financial institution that is associated with a Balinese customary village. LPDs face competing pressures to both maintain their traditional character and align themselves with national standards for financial management. This article establishes the hybrid legal character of LPDs (under Balinese customary law and Indonesian national law) in order to analyse their evident shortcomings, being the vulnerability of some monitoring and protection systems to misappropriation. We rely on normative legal research methods, including statutory analysis and analysis of case studies. We examine the LPD Regulations and Balinese customary law, supplemented by interviews on issues of relevance. We conclude that the recognition of LPDs under the law, given the fundamental basis of the LPD in the customary village, ought to be given primacy to their status under Balinese customary law. However, the monitoring and protection systems of LPDs must be improved and uniform standards must be enforced – otherwise, their customers will simply use other financial institutions. We also conclude that it is possible to improve management practices while respecting the autonomy of customary villages. Therefore, we assert that properly implemented measures will make a direct intervention from government unnecessary.